The Ghost Map Guide for English 100 - Kansas State University, K-State First (Kansas State University. K-State First., 2014)
Created for English 100: Introduction to Expository Writing, this guide provides instructors ideas and resource for using "The Ghost Map" by Steven Johnson in their classes. Included in the guide are chapter excerpts, connection questions, and keywords.
Keywords: Ghost Map, The; Guide; Common reading program; First-year experience program; First-year seminars; English 100; Brochures